Teaching an old drug new tricks: Regulatory insights for the repurposing of hemin in cardiovascular disease - Ashley L. Eadie; Jeremy A. Simpson; Keith R. Brunt (Wiley, 2024)
Abstract Drug repurposing has gained significant interest in recent years due to the high costs associated with de novo drug development; however, comprehensive pharmacological information is needed for the translation of pre‐existing drugs across clinical applications. In the present study, we explore the current pharmacological understanding of the orphan drug, hemin, and identify remaining knowledge gaps with regard to hemin repurposing for the treatment of cardiovascular disease. Originally approved by the United States Food and Drug Administration in 1983 for the treatment of porphyria, hemin has attracted significant interest for therapeutic repurposing across a variety of pathophysiological conditions. Yet, the clinical translation of hemin remains limited to porphyria. Understanding hemin's pharmacological profile in health and disease strengthens our ability to treat patients effectively, identify therapeutic opportunities or limitations, and predict and prevent adverse side effects. However, requirements for the pre‐clinical and clinical characterization of biologics approved under the U.S. FDA's Orphan Drug Act in 1983 (such as hemin) differed significantly from current standards, presenting fundamental gaps in our collective understanding of hemin pharmacology as well as knowledge barriers to clinical translation for future applications. Using information extracted from the primary and regulatory literature (including documents submitted to Health Canada in support of hemin's approval for the Canadian market in 2018), we present a comprehensive case study of current knowledge related to hemin's biopharmaceutical properties, pre‐clinical/clinical pharmacokinetics, pharmacodynamics, dosing, and safety, focusing specifically on the drug's effects on heme regulation and in the context of acute myocardial infarction.